Jenny Thompson at 90 m of Her Gold Medal 100 m Race at the 1999 Pan Pacific Championships in Sydney - Rushall, B. S.
Video pictures (15 frames) and the appropriate technical/ biomechanical explanations for Jenny Thompson at 90 m of Her Gold Medal 100 m Race at the 1999 Pan Pacific Championships in Sydney.